2014
DOI: 10.5350/dajpn2014270205
|View full text |Cite
|
Sign up to set email alerts
|

Demansı olmayan Parkinson hastalarında işitsel olaya bağlı potansiyel (P300) ile kognitif fonksiyonların değerlendirilmesi

Abstract: Objective: Idiopathic Parkinson's disease is a clinical situation characterized by akinesia, rigidity, and tremor, and results from the degeneration of the dopaminergic nervous system. As the disease progresses over time, depression, cognitive dysfunction and alterations in cognitive functions are added to the movement disorder at varying rates. The P300 component is a useful parameter for cognitive processing studies on PD patients, as it is independent from motor skills. The current study aimed to show the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…In their study, Prabhakar et al also stated that P300 latency was not prolonged in the early stages of the illness [14]. In contrast to the findings of the aforementioned research, Sarikaya et al, Lopes et al, and Tokic et al found that the P300 wave's latency was significantly delayed when compared to the control group [2,10,11]. These conflicting results have been highlighted by many authors in their works [12,14].…”
Section: Discussionmentioning
confidence: 95%
“…In their study, Prabhakar et al also stated that P300 latency was not prolonged in the early stages of the illness [14]. In contrast to the findings of the aforementioned research, Sarikaya et al, Lopes et al, and Tokic et al found that the P300 wave's latency was significantly delayed when compared to the control group [2,10,11]. These conflicting results have been highlighted by many authors in their works [12,14].…”
Section: Discussionmentioning
confidence: 95%